Extragalactic integral field spectroscopy on the Gemini telescopes - Bunker, A; Smith, J; Parry, I; Ben Metcalf, R; Sharp, R; de Grijs, R; Bower, R; Swinbank, M (2006)
We have undertaken a programme on the Gemini 8-m telescopes to demonstrate the power of integral field spectroscopy, using the CIRPASS instrument in the near-infrared. Here, we present some of our results from 3D spectroscopy of extra-galactic objects: mapping the Hα velocity field in a z ≈ 1 disc galaxy; exploring dark matter sub-structure through observations of an Einstein cross gravitational lens; and the star formation time-scales of young massive clusters in a starburst galaxy. © 2006 Elsevier B.V. All rights reserved.